The Effectiveness of Foot Massage on Fatigue in Breast Cancer Patients Undergoing Chemotherapy - Ekaputri, Mersi; Alwi, Fahrizal; Harahap, Mery Silvia; Laiya, Maria Gracesella Elsy; Silalahi, Rini Debora (Jurnal Penelitian Keperawatan Medik, 2025)
Breast cancer is a significant global health issue with a rising incidence in Indonesia. Patients undergoing chemotherapy often experience fatigue as a common side effect of treatment. This study aimed to examine the effect of foot massage on reducing fatigue among breast cancer patients receiving chemotherapy at RSU Sembiring Deli Tua. A quantitative approach was employed using a quasi-experimental design with a one-group pretest-posttest framework. Eighteen breast cancer patients undergoing chemotherapy participated in this study. Fatigue levels were measured before and after the foot massage intervention using the Fatigue Assessment Scale (FAS). The results demonstrated a reduction in fatigue levels following the foot massage intervention. Statistical analysis using the Wilcoxon Signed Rank Test revealed a significant difference in fatigue levels before and after the intervention (p = 0.002; p<0.05). The majority of participants experienced a decrease in fatigue from moderate to mild, while six participants showed no significant change. These findings are consistent with previous studies indicating the effectiveness of foot massage in alleviating fatigue among breast cancer patients. In conclusion, foot massage can be considered an effective complementary therapy for reducing fatigue in breast cancer patients undergoing chemotherapy in Indonesia.